QUALITY OF WORK LIFE AMONG LECTURERS WORKING IN MEDICAL FIELD - Dewi, Rooswita Santia; Aslamiah, Aslamiah; Noorhapizah, Noorhapizah; Novitawati, Novitawati (Pendidikan Guru Pendidikan Anak Usia Dini (PG PAUD) Universitas Lambung Mangkurat, 2024)
The dynamic era of globalization requires workers and companies to always develop new products and innovate according to society's needs and market demands. The field of higher education is no exception where lecturers are required to accept a workload that can often damage the quality of their work life. This research aims to determine the quality of work life of lecturers who teach at the Faculty of Medicine and work in the medical field. This research uses a quantitative approach and descriptive analysis to provide an overview of the level of quality of work life. The research results show that the quality of work life of the majority of lecturers who are research subjects is at a high level. This is influenced by the score obtained on the salary and status dimensions which are related to the salary and status obtained by the research subjects from they work and also from society regarding the work they have.